Pilot development and initial validation of the Black spiritual creativity scale - Drake, Danielle (Journal of spirituality in mental health, 2025)
There is a lack of research dedicated to understanding and evaluating how African Americans engage in spiritual creativity as a form of cultural empowerment in order to thrive in the face of systemic oppression. The Black Spiritual Creativity Scale (BSCS) is a new measure that was designed to address this gap in the literature. The BSCS measures the experience of creativity, rhythm, and soul as spiritual forces that contribute to a sense of personal transformation as well as resistance and liberation among African Americans. The present pilot exploratory factor analysis study was conducted with a pilot sample of 126 participants and produced a 15-item, two-factor model. Reliability and validity analyses supported the initial promise of this new scale. Future research implications are discussed.